Identification of B-cell epitopes of Indian Zika virus strains using immunoinformatics - Roy, Rohan Raj; Tadkalkar, Nitali; Deshpande, Gururaj Rao; Atre, Nitin M.; Shil, Pratip; Sapkal, Gajanan (Frontiers in Immunology, 2025)
IntroductionThe Zika virus is an emerging Flavivirus known to cause Zika infection in humans. It is associated with severe health problems such as microcephaly and Guillain-Barré syndrome post the Brazilian epidemic in 2015-16. The spread of the Zika virus to the Asian subcontinent, especially to India is a matter of great concern. Two recent co-circulating Indian Zika virus strains such as Rajasthan and Maharashtra detected in 2018 and 2021 were studied to identify B-cell epitopes in the envelope and non-structural 1 protein as these epitopes are major indicators of robust humoral immune response. The study aimed at identifying novel epitopes, followed by molecular docking with potent Zika virus-specific monoclonal antibodies. The novel epitopes identified in this study shall be essential in designing multi-epitope vaccines capable of inducing antibody response against Zika virus infection.MethodsABCpred, BepiPred 2.0 and Kolaskar-Tongaonkar methods were used for predicting the linear B-cell epitopes, and Discotope 2.0 and ElliPro were used for the prediction of conformational epitopes. Linear epitopes were further checked for protective antigenicity, allergenicity and toxicity. Based on the stringent study design criteria, only the novel epitopes were considered for molecular docking with complementary determining regions of potent Zika virus-specific monoclonal antibodies.ResultsNineteen linear and five conformational epitopes were shortlisted based on protective potential, non-allergic and non-toxic properties for Zika virus E protein, from which nine linear and three conformational epitopes were identified as novel. Molecular docking studies revealed that the novel linear epitopes, one each from EDIII, EDII, EDI and EDI/DIII hinge were involved in epitope-CDR interactions with potent neutralizing Zika virus E-specific mouse monoclonal antibody ZV-67. Moreover, the novel EDII epitope was exclusively engaged in epitope-CDR interactions of potent neutralizing Zika virus E-specific human monoclonal antibody Z3L1. None of the linear epitopes of Zika virus NS1 were ascertained as novel based on our study criteria. Conformational epitopes were identified as novel for NS1 protein.ConclusionThis study identified Zika virus-specific novel epitopes of envelope and non-structural -1 proteins in the currently co-circulating Indian strains. Furthermore, in-silico validation through molecular docking added insight into antigen-antibody interactions, paving way for future in vitro and in vivo studies.